2018
DOI: 10.4236/pp.2018.911037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Measured Trough Values after Deriving the Initial Dose Setting of Vancomycin with a Conventional Computer Software and a Nomogram Based on the Revised Japanese 2016 Therapeutic Drug Monitoring Guidelines for Antimicrobial Agents

Abstract: Background: Due to the relatively high renal toxicity of vancomycin injection (VCM), setting an initial dose that achieves a trough that ranges between 10 and 20 μg/mL on day 3 is important to ensure safety and minimize side-effects, especially for patients with low renal function. To address these issues, the revised 2016 Therapeutic Drug Monitoring (TDM) Guidelines for Antimicrobial Agents (GL2016) proposed the use of a renal function-based, estimate glomerular filtration rate (eGFR) nomogram for setting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…5,6 We previously reported that mean measured VCM trough values in the patients treated according to established guidelines were generally lower compared with the patients treated not according to established guidelines. 11 In other words, although using the GL2016 nomogram is associated with enhanced safety, it might reduce clinical efficacy. In order to correct this issue, the GL2016 added an amendment that recommended an initial loading dose of VCM that is slightly higher than that typically given on the first day, in order to enhance clinical efficacy on day 1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,6 We previously reported that mean measured VCM trough values in the patients treated according to established guidelines were generally lower compared with the patients treated not according to established guidelines. 11 In other words, although using the GL2016 nomogram is associated with enhanced safety, it might reduce clinical efficacy. In order to correct this issue, the GL2016 added an amendment that recommended an initial loading dose of VCM that is slightly higher than that typically given on the first day, in order to enhance clinical efficacy on day 1.…”
Section: Discussionmentioning
confidence: 99%
“…12 In our previous study, when patients with different severities of renal dysfunction were compared, groups with low renal function had trough VCM levels within the range of adequate blood concentrations when we performed the nomogram-guided monitoring recommended by the GL2016. 11 Masuda et al retrospectively calculated the eGFR of patients after establishing the initial VCM dose using the computer software for calculation of VCM trough concentration evaluated the efficacy and safety of the dosage recommended by the nomogram, and suggested that an eGFR of between 30 and 80 mL/min/1.73 m 2 might prevent achievement of an adequate blood concentration of VCM. 17 Suzuki et al retrospectively examined the proportion of patients who achieved the recommended trough levels in the GL2016 group and found that 27.9% of the subjects in the TDM implementation group achieved a trough level ranging between 10 and 15 μg/mL, although 11.6% of the subjects had trough levels that exceeded 20 μg/mL, similar to the results of our previous study (31%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations